Sobreprotección Y Desarrollo Psicosocial en estudiantes de la Unidad Educativa “Miguel Ángel León Pontón”. Riobamba. Marzo-Julio 2017 - Quezada Vacacela, Grety Esperanza (2018)
The present research work seeks to determine how the overprotection relates to the psychosocial development of the students, since it is a subject of great interest, considered one of the most common impediments in the optimal progress of children. Theoretical framework is based on the independent variable such as overprotection, which is the excessive care of parents towards their children and the dependence variable psychosocial development, which is a process of orderly and stepwise change, which achieved by the interaction with the environment. The methodology was based on non-experimental design. The type of research correspond to descriptive and correlational, the scientific method was applied through the analytical and synthetic process, for this study was selected a population of 30 students and 30 parents of the First Year of Basic Education, parallel “A” of Unidad Educativa “Miguel Ángel León Pontón” The sample was intentionally non-probabilistic. The techniques used were the survey and observation sheet. As a result, is that overprotection and psychosocial development have a low positive relationship, since parents in a certain way did not recognize the overprotection they exert in their lives since their answers do not match according to the children´s attitudes.